Leveraging supplier capabilities: The role of locus of capability deployment - Weigelt, Carmen (Strategic Management Journal, 2013)
Abstract This study adds to the resource‐based view by studying how client firms may gain performance benefits from supplier IT capabilities in market‐based arrangements where the supplier's IT capabilities are readily available to multiple client firms. I argue that the locus of supplier capability deployment, i.e. whether supplier capabilities are deployed at the client (in‐sourcing) or supplier (outsourcing), has implications for client firm performance. The findings show that in‐sourcing leads to complementary effects between supplier IT capabilities and client operational capabilities. In contrast, clients with weaker operational capabilities benefit from outsourcing the respective activity to the supplier, and may even be able to reduce their capability disadvantage through outsourcing. The data on 964 U.S. credit unions contracting with 22 technology solution providers is archival. Copyright © 2012 John Wiley & Sons, Ltd.